Origin, evolution and assessment of the hydrogeochemical functioning of a thermal mineral spring in Batna (Eastern Algeria) - ATHAMENA, Ali; BELALITE, Halima; AOUISSI, Hani Amir; ATHAMENA, Malika; BOUGHEDIRI, Mabrouk; LAAMOURI, Bachir; GAAGAI, Aissam; KEBAILI, Feriel Kheira; BENSELHOUB, Aissa (Наукові записки Сумського державного педагогічного університету ім. А.С. Макаренка. Географічні науки, 2025)
A hydrogeological study of the thermal source of Ouled Aïcha in the Aurès Mountains showed that the source emerges in a particular natural context mainly represented by the presence of a vertical fault in the NE-SW direction affecting Cretaceous limestone. This supports the increase on the surface of moderately hot water, whose temperature is approximately 30 °C and an exploited flow of 3 L s-1. The vertical electric sounding in situ showed the in-depth presence of a saliferous conducting level within a calcareous-resistant mass, which probably settled in the fault's favor. The presence of this saliferous level strongly influences the hydrochemistry of this thermal source. Thus, the water from the source is characterized by high salinity due to its temperature, which favors the dissolution of mineral salts in sufficient quantity throughout its journey (12390 µS/cm). The high concentrations of chlorides, sodium and sulfates indicate a significant contribution of salt from evaporitic formations as for the calcium content indicates that this water is influenced by the dissolution of carbonate formations. These physicochemical characteristics provide this water therapeutic virtue, which can be attributed to its chemical composition, high rock salt content, and low nitrate content. Geothermometry has shown that these thermal waters acquire a high temperature in their original tanks coming from a depth through a fault system that affects the basement.